“Aplicación de registros odontológicos en la identificación forense. grupo de operaciones especiales del cantón Riobamba, 2019 - Leydi Dayana, Padilla Padilla (2020)
This investigation focuses on forensic dentistry field. Its objective is to prove dental diversity existence among each individual’s records. The studied population came from Special Operations Group - Riobamba (National Police) due to their constant exposure to catastrophes (incineration, putrefaction among others) in their work performance. The data collection was based on the observation of clinical histories (odontogram) and panoramic radiography, information that was documented in the forensic odontological card. Later on, the studied population was analyzed by means of the five stages, each one of the 32 dental pieces. A comparison was made between pairs of all the possible combinations (465) within the presented dental patterns. A greater frequency of restorations and loss of teeth was observed in the studied population. The diversity was calculated by determining a value of 1 when differences were observed in a pair comparison. A value of 0, if there were no differences between the set of records. The result obtained was a diverse value of 1 of the dental records. It indicates the uniqueness of the dental characteristics from one individual to another. To sum up, dental records are unique to each human being and this information can be used as a method of identification in the forensic sciences